2015
DOI: 10.1021/jacs.5b01913
|View full text |Cite
|
Sign up to set email alerts
|

Mono-Oxidation of Bidentate Bis-phosphines in Catalyst Activation: Kinetic and Mechanistic Studies of a Pd/Xantphos-Catalyzed C–H Functionalization

Abstract: Kinetic, spectroscopic, crystallographic, and computational studies probing a Pd-catalyzed C-H arylation reaction reveal that mono-oxidation of the bis-phosphine ligand is critical for the formation of the active catalyst. The bis-phosphine mono-oxide is shown to be a hemilabile, bidentate ligand for palladium. Isolation of the oxidative addition adduct, with structural elucidation by X-ray analysis, showed that the mono-oxide was catalytically competent, giving the same reaction rate in the productive reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
73
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(88 citation statements)
references
References 88 publications
7
73
1
1
Order By: Relevance
“…In 2015, in the contexto f am echanistic investigation of Pd 0 -catalyzed CÀHa rylations mediated by Xantphos, Blackmond and co-workers revealed that the monooxidation of the P, P-ligand, which leads to corresponding bis-phosphine mono-oxide (BPMO), is crucial for the formationo ft he active catalyst. [86] As ar esult,X antphos monooxide performs as ah emilabile P, O-ligand, which affords additional coordinationf or an internal CMD base (Figure 4). As a consequence, andk nowing that the reduction of Pd II precatalysts such as Pd(OAc) 2 is accompanied by the oxidation of a phosphine in the corresponding monooxide, [87] chiral P, P-ligands reported thereafter in conjunction with ap alladium(II) source should not likely be considered as the actual ligands that participate in the catalytic cycle.…”
Section: Bidentate and Hemilabile Ligandsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2015, in the contexto f am echanistic investigation of Pd 0 -catalyzed CÀHa rylations mediated by Xantphos, Blackmond and co-workers revealed that the monooxidation of the P, P-ligand, which leads to corresponding bis-phosphine mono-oxide (BPMO), is crucial for the formationo ft he active catalyst. [86] As ar esult,X antphos monooxide performs as ah emilabile P, O-ligand, which affords additional coordinationf or an internal CMD base (Figure 4). As a consequence, andk nowing that the reduction of Pd II precatalysts such as Pd(OAc) 2 is accompanied by the oxidation of a phosphine in the corresponding monooxide, [87] chiral P, P-ligands reported thereafter in conjunction with ap alladium(II) source should not likely be considered as the actual ligands that participate in the catalytic cycle.…”
Section: Bidentate and Hemilabile Ligandsmentioning
confidence: 99%
“…Despite the fact that diphosphine ligands were employed in various Pd‐catalyzed C−H activation reactions, their exact role remained unknown for a long time. In 2015, in the context of a mechanistic investigation of Pd 0 ‐catalyzed C−H arylations mediated by Xantphos, Blackmond and co‐workers revealed that the monooxidation of the P,P‐ligand, which leads to corresponding bis‐phosphine mono‐oxide (BPMO), is crucial for the formation of the active catalyst [86] . As a result, Xantphos mono‐oxide performs as a hemilabile P,O‐ligand, which affords additional coordination for an internal CMD base (Figure 4).…”
Section: Bidentate and Hemilabile Ligandsmentioning
confidence: 99%
“…Finally, given Eastgate and Blackmond’s recent report of reactions catalyzed by mono-oxidized bidentate XANTPHOS and palladium, [9] we wanted to determine if such species might be involved in the arylation reactions outlined herein. To address this issue, we employed the Buchwald precatalyst [10] with NIXANTPHOS ligand, which generates Pd(0) by reductive elimination (Scheme 6).…”
mentioning
confidence: 99%
“…The successful use of phosphines in oxidative C−H carbonylation is surprising given their propensity towards oxidation to phosphine oxides; the unique effect of xantphos, compared to other phosphines, is also striking. Accordingly, we found that a reaction using xantphos monooxide gave almost the same yield as the use of xantphos (entry 10);, however, the yield dropped dramatically when xantphos dioxide was used (entry 11) . While we are unsure of its precise role, we believe that xantphos (or its monooxide) most likely stabilizes Pd 0 at the end of the catalytic cycle prior to oxidation to the Pd II species required for the reaction …”
Section: Methodsmentioning
confidence: 98%